To solve the system of equations using substitution, we start with the following equations:
- \( 2.5x + y = -2 \)
- \( 3x + 2y = 0 \)
Step 1: Solve one equation for one variable
Let's solve the first equation for \( y \):
\[ y = -2 - 2.5x \]
Step 2: Substitute into the second equation
Now we'll substitute \( y \) into the second equation:
\[ 3x + 2(-2 - 2.5x) = 0 \]
Distributing the \( 2 \):
\[ 3x - 4 - 5x = 0 \]
Step 3: Combine like terms
Combine the \( x \) terms:
\[ -2x - 4 = 0 \]
Step 4: Solve for \( x \)
Add 4 to both sides:
\[ -2x = 4 \]
Divide by -2:
\[ x = -2 \]
Step 5: Substitute back to find \( y \)
Now use this value of \( x \) to find \( y \):
\[ y = -2 - 2.5(-2) \]
Calculating:
\[ y = -2 + 5 = 3 \]
Step 6: Write the solution
The solution to the system of equations is:
\[ (x, y) = (-2, 3) \]
Thus, the correct response from the options given is:
(−2, 3).